Designing IELTS Writing Material for Learners with Low Level of English Proficiency Based on Needs Analysis - Ahmad Farid; Muhammad Saifuddin (Journal of Research in Foreign Language Teaching (JRFLT), 2018)
Designing IELTS Writing for learners with low level of English Proficiency needs a good needs analysis. It was because the teaching material should meet learners’ needs and consider their weaknesses. This reasearch was intended to design IELTS Writing teaching material for lecturers whose English proficiency was still low. Needs analysis was conducted to identify respondents’ common errors and weaknesses. Respondents took writing test which consisted of two tasks; task 1 and task 2. From the data analysis, it was found that there were 10 most common errors in task 1 and 8 most common errors in task 2. Summarizing the most common errors in task 1 and task 2, they were considered based on the most respondents’ errors and essay structure was the main common error respondents did. Furthermore, the design of IELTS Writing teaching material considered the findings as the basis of material design.